Kekeringan Meteorologi Di Kabupaten Bengkalis - Mohtar Anwar; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Weather and climate dynamics play a major role in spatial and temporal changes in groundwater availability. Temporally, groundwater availability changes are easier to feel such as the incidence of drought phenomena and water shortages that occur during certain months. This index is a benchmark to see the potential for fire in peatlands. This research was conducted in the Bengkalis regency of Riau Province using the method Keetch-Bryam Drought Index (KBDI). Peat fires can transform peatlands into farmland and settlements. The results of the drought Index analysis, the highest drought index value of the KBDI method occurred on Grid 8 in March 2016 of 1894.88 with extreme classification. The main factor for the occurrence of meteorological dryness is rainfall. Value of KBDI The higher the more the extreme. So the increase rainfall followed by decreasing the value of KBDI. The higher the temperature the greater the drought index value of the KBDI.Keywords: KBDI, Drought, Peatland Fire